Antioxidant activities of ginger extract and its constituents toward lipids. (15th January 2018) - Si, Wenhui; Chen, Yan Ping; Zhang, Jianhao; Chen, Zhen-Yu; Chung, Hau Yin
Highlights: Ginger extract (GE) and four components exhibited antioxidant properties. The properties were attributable to hydroxyl groups and solubilizing side chains. 6-Shogaol and 10-gingerol performed better at 60 °C than 6-gingerol and 8-gingerol. GE displayed the strongest dose-dependent antioxidant properties at 60, 90, & 120 °C. GE can be used as a natural antioxidant in lipid-containing processed foods. Abstract: Lipid oxidation—a major cause of food product deterioration—necessitates the use of food additives to inhibit food oxidation. Ginger extract (GE) has been reported to possess antioxidant properties. However, components isolated from ginger have been rarely reported to inhibit fat oxidation. Herein, antioxidant properties of GE and four pure components derived from it (6-gingerol, 8-gingerol, 10-gingerol, and 6-shogaol) were examined and their properties were compared to those of butylated hydroxytoluene. GE and the constituent components exhibited antioxidant properties that might be attributed to their hydroxyl groups and suitable solubilizing side chains. 6-Shogaol and 10-gingerol exhibited higher activity at 60 °C than 6-gingerol and 8-gingerol. Low antioxidant activity was detected at high temperatures (120/180 °C). Overall, GE displayed the strongest dose-dependent antioxidant properties, especially at high temperatures, thereby demonstrating that GE can be employed as a natural antioxidant in lipid-containing processed foods.